2011
DOI: 10.1142/s1088424611003781
|View full text |Cite
|
Sign up to set email alerts
|

The trisubstituted-triazole approach to extended functional naphthalocyanines

Abstract: Recently, a novel modular approach to octatriazole-derived phthalocyanines (Pcs; 1) was developed and optimized in our group; herein, the pool of the functional Pc materials was expanded for an additional candidate (2), a fused derivative of 1. Compared with 1, the aromaticity in 2 is extended by an additional four benzene and eight triazole rings and, in addition, the triazole units and the Pc core co-create four functional, in-plane cavities. Various methods to link the unsubstituted carbon atoms of the neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similar calculations with [CuCl(IPr)] as catalyst revealed that the barrier in this case slightly higher ([11]#, 28.4 kcal/ mol), but this transition state is considerably stabilized when compared to [13]# as well as compared to its regioisomer leading to the formation of a 4-I-triazole 2a ([12]#, 34.1 kcal/ mol) (see Scheme 8 and Table 7).…”
Section: ■ Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar calculations with [CuCl(IPr)] as catalyst revealed that the barrier in this case slightly higher ([11]#, 28.4 kcal/ mol), but this transition state is considerably stabilized when compared to [13]# as well as compared to its regioisomer leading to the formation of a 4-I-triazole 2a ([12]#, 34.1 kcal/ mol) (see Scheme 8 and Table 7).…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Tris-triazoles, and TTTA in particular, remain the most popular ligands for this reaction, 11 and the only ones that have found application in larger systems, such as the functionalization of polymers 12 and preparation of phthalocyanines. 13 Despite its efficiency, important drawbacks remain for the general use of this family of ligands in this transformation. First of all, contrary to copper salts, tris-triazole compounds are extremely expensive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This strategy was used as a key step in the synthesis of new planar octatriazole-derived naphthalocyanine (Nc) 124 functionalized by TIPS-protected ethynyl groups. 50 The intramolecular homocoupling was performed with 1,2bis(5-iodotriazol-4-yl)-4,5-dimethoxybenzene 122 affording the desired polyaromatic ditriazole compound 123 in 45% yield. The latter was converted into final Nc 124 in four steps (Scheme 31).…”
Section: Scheme 30 the Synthesis Of Polyaromatic Systems Based On Fusmentioning
confidence: 99%
“…However the term CuAHAC (Cu-catalyzed azide-haloalkyne cycloaddition) is also in use. 49,50 Cu (I) R R Cu (I) "I + "-source amine…”
Section: Introductionmentioning
confidence: 99%